The Evaluasi Kekuatan Runway 17/35 Menggunakan Metode FAA di Bandar Udara Internasional Komodo - Darmawan, Muhammad Zhabri Gaffari; Deanur Rahmat Julainsyah (Unmuh Babel Press, 2024)
This study evaluates the strength of runway 17/35 at Komodo International Airport using the FAA method and COMFAA V3.0 software. The goal is to determine the Pavement Classification Number (PCN) to optimize the operational capacity of the runway. Runway 17/35 has a length of 2,650 meters and a width of 45 meters, with asphalt pavement. The 2017 Heavy Weight Deflectometer (HWD) test showed a PCN value of 55 F/C/X/T. Aircraft movement data from 2016 to 2020 identified ten main types of aircraft frequently operating, with the B737-800 having the highest Aircraft Classification Number (ACN) of 50 and a Maximum Takeoff Weight (MTOW) of 73,016 kg. The PCN was calculated for three runway segments based on material and layer thickness, showing evaluation thicknesses for segments A, B, and C of 873 mm, 981 mm, and 1123 mm, respectively. The overall calculated PCN value is 52 F/C/X/T. Comparison between the existing PCN value (55 F/C/X/T) and the calculated value (52 F/C/X/T) shows a minor difference. The ACN values of all aircraft operating at this airport do not exceed the runway's PCN value, indicating that runway 17/35 is sufficiently strong to accommodate all these aircraft, including the B737-800. This evaluation ensures the safety and efficiency of flight operations at Komodo International Airport and supports the enhancement of long-haul flight service capacity in the future